Full penetration welding of thick high tensile strength steel plate with high-power disk laser in low vacuum. Issue 5 (4th May 2018) - Katayama, Seiji; Ido, Ryouji; Nishimoto, Koji; Mizutani, Masami; Mizutani, Yousuke
ABSTRACT: This study was undertaken in order to investigate the effect of reduced ambient pressure from an atmospheric pressure (101 kPa) to 0.1 kPa on one-pass full penetration welding of thick high-tensile strength steel plate of 23 mm thickness. A 16 kW disk laser of 1030 nm in wavelength was employed to weld HT980 grade plates at the speed of 5–25 mm/s. In partial penetration welding, it was revealed that humping phenomena occurred easily. Full penetration welding of the high-tensile strength steel plates could not be achieved at 101 kPa. On the other hand, full penetration welding was obtained at the welding speed of less than 20 mm/s at the pressure of less than 10 kPa. Especially, at 0.1 kPa, and 17 and 20 mm/s, sound weld joints without defects were obtained. According to the observation results of a keyhole inlet and a surface molten pool during welding with a high-speed video camera, the melt in front of a keyhole was smaller and the behaviour of a keyhole and a plume was much more stable at 0.1 kPa than at 101 kPa. Moreover, in the full penetration welding, spattering was suppressed under the proper conditions. Such phenomena became more stable in fast welding. It was revealed in laser welding of thick high-tensile strength steel plates that the formation of narrow I-shaped weld beads by achieving full-penetration welding in low vacuum was essential for the production of sound welds without defect.